Labor Picketing Centre Plaza Holiday Inn - Watkins, Howard::::::::: (1983)
Howard Watkins holding two signs "Hammonds Betrays Taxpayers Hotel Centre Plaza hotel entrance and Selland Arena in background; Ventura Street side